3D radiative transfer simulations of Eta Carinae's inner colliding winds - II. Ionization structure of helium at periastron - Clementel, Nicola; Madura, T. I.; Kruip, C. J. H.; Paardekooper, Jan-Pieter (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. Spectral observations of the massive colliding wind binary Eta Carinae show phase-dependent variations, in intensity and velocity, of numerous helium
Gesehen am 01.12.2020